PENGARUH PENAMBAHAN DOSIS RAFINOSA DALAM PENGENCER TRIS KUNING TELUR TERHADAP MOTILITAS, PERSENTASE HIDUP DAN ABNORMALITAS SPERMATOZOA SAPI ONGOLE - Iis Nurlia; Sri Suharyati; Madi Hartono (JURNAL ILMIAH PETERNAKAN TERPADU, 2016)
The research was conducted on May 16—18 at the Laboratory of Technical Services Unit Regional Artificial Insemination Central Lampung, using semen from  Ongole cattle. aims of this research were determine the effect of different doses of rafinose and determine the optimal doses rafinosa in tris  yolk diluent for motility, percentage of live and abnormalities spermatozoa Ongole cattle. The experimental design used  completely randomized design with 6 treatments rafinosa doses (0,5%;  1,0%,  1,5%;  2,0%;  2,5%;  3%) in tris yolk diluent with 4 times replications. The data were analyzed using  analysis of varian with 5% or 1% significance level. Significantly different results was further tested by orthogonal polynomials.  The results showed that the addition of rafinosa doses effect were not significantly different (p>0.05) on percentage motility after prefreezing and Post Thawing Motility, the percentage of live sperm Post Thawing Motility, and the percentage of abnormal spermatozoa after equilibration, prefreezing, and Post Thawing Motility, but the effect is very significantly (p<0.01) on percentage motility spermatozoa after equlibration and percentage of live spermatozoa after prefreezing. Addition doses of rafinose significant effect (p <0.05) on the percentage of live sperm after equilibration. Addition doses rafinose based pattem ortogonal polinomial regression on percentege motility after equilibration with equations ӯ = 65,58-2,36x, the persentage of live sperm after equilibration with aquations ӯ=81,23-4,47x, and the persentage of live sperm after prefreezing with aquations ӯ=79,13-4,68x. Keywords :Rafinosa , Egg Yolk Tris, Motility, Percentage of Live, Abnormalities, Ongole Cattle